2015
DOI: 10.1088/0031-8949/90/2/025402
|View full text |Cite
|
Sign up to set email alerts
|

Search for environmental effects on the KLL Auger spectrum of rubidium generated in radioactive decay

Abstract: The KLL Auger spectrum of rubidium following the electron capture (EC) decay of 83 Sr and 85 Sr isotopes was experimentally studied in detail for the first time using one 83 Sr source and three 85 Sr sources in different host matrices. Energies, relative intensities, and natural widths of all the nine well-resolved basic spectrum components were determined and compared with both predictions and experimental data for krypton. The results of our multiconfiguration Dirac-Fock calculations demonstrated an influen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…The starting approximations were obtained from suitable components of the evaluated spectrum. More details on the approach used can be found, e.g., in [23]. The position, the height, and the width of each fitted spectrum line, the constant background and the width of the spectrometer response function were the fitted parameters.…”
Section: Spectra Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…The starting approximations were obtained from suitable components of the evaluated spectrum. More details on the approach used can be found, e.g., in [23]. The position, the height, and the width of each fitted spectrum line, the constant background and the width of the spectrometer response function were the fitted parameters.…”
Section: Spectra Evaluationmentioning
confidence: 99%
“…However, such data are of considerable importance for basic research as well as for interpretation of weak structures observed in very complex experimental Auger electron spectra. It was, moreover, found in the experimental investigations (see, e.g., [22,23]) that energies of the KLL Auger electrons are a quite sensitive probe of changes in local atomic environment. In [22], the krypton KLL Auger spectrum accompanying the electron capture (EC) decay of 83 Rb incorporated in two different solid hosts (a bulk of a high purity polycrystalline Pt foil and a layer evaporated in vacuum on the same type of Pt foil) was studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…KLL Auger spectrum calculated using the MCDHF method is compared to experimental data from Ref. [42]. Spectral profile of individual component (in solid line) is evaluated from the measured spectrum using the computer code described in Ref.…”
Section: Future Directionsmentioning
confidence: 99%